2010
DOI: 10.1111/j.1467-7652.2010.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting plants for glutathione (GSH) production: Uncoupling GSH synthesis from cellular controls results in unprecedented GSH accumulation

Abstract: Summary Glutathione (GSH) is a key factor for cellular redox homeostasis and tolerance against abiotic and biotic stress (May et al., 1998; Noctor et al., 1998a). Previous attempts to increase GSH content in plants have met with moderate success (Rennenberg et al., 2007), largely because of tight and multilevel control of its biosynthesis (Rausch et al., 2007). Here, we report the in planta expression of the bifunctional γ‐glutamylcysteine ligase—glutathione synthetase enzyme from Streptococcus thermophilus (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 61 publications
1
45
0
1
Order By: Relevance
“…No lesions were observed in poplar (Populus sp.) with similar increases in tissue glutathione (Noctor and Foyer, 1998), and it has recently been shown that very high glutathione contents can be engineered in tobacco without major detrimental effects on plant development (Liedschulte et al, 2010). Thus, the available data suggest that high levels of glutathione can be tolerated by plants and are not in themselves sufficient to trigger cell death pathways.…”
Section: Oxidative Stress Glutathione Ascorbate Cell Division Celmentioning
confidence: 99%
“…No lesions were observed in poplar (Populus sp.) with similar increases in tissue glutathione (Noctor and Foyer, 1998), and it has recently been shown that very high glutathione contents can be engineered in tobacco without major detrimental effects on plant development (Liedschulte et al, 2010). Thus, the available data suggest that high levels of glutathione can be tolerated by plants and are not in themselves sufficient to trigger cell death pathways.…”
Section: Oxidative Stress Glutathione Ascorbate Cell Division Celmentioning
confidence: 99%
“…2004; Mullineaux and Rausch, 2005;Liedschulte et al, 2010). Transgenic Arabidopsis plants with low GSH level (10% of the wild type) exhibit hypersensitivity to cadmium stress due to the limited capacity of these plants to make phytochelatins (Xiang et al, 2001).…”
mentioning
confidence: 99%
“…Although jah2 has only 4.5 times more g-EC than the normal amount of GSH, and g-EC level in jah2 pad2-1 is equal to that of GSH in the wild type, both are compromised in growth. By contrast, GSH up to 20-fold higher than normal in transgenic tobacco (Nicotiana tabacum) plants expressing a bifunctional g-EC-ligase/ GSH-S had no phenotypic effect (Liedschulte et al, 2010). On the other hand, overexpression of a g-ECligase in tobacco resulting in up to 25-fold elevated g-EC yielded plants displaying pathogenesis-related necrotic lesions, although these plants also had 3 to 5 times the normal GSH level (Creissen et al, 1999).…”
Section: Discussionmentioning
confidence: 99%